The Power Dynamics Of International Mediation - ElAhmadieh, Najd (2023)
World history has been shaped by myriad of conflict. Therefore, conflict resolution tools were developed. However, the emergence of intractable conflict required a development in the concept of mediation. This study tackles the Palestinian Israeli conflict as an example of intractable conflicts and evaluates the American mediation efforts to solve the conflict. Utilizing an interplay of structuralist and complex constructivist approach, and to better understand the power dynamics of the American mediation in the negotiation process, the study focuses on three main accords; Camp David, Oslo/Camp David Summit, and Abrahamic Accords. The research hypothesizes that the intractability and complexity of the Palestinian - Israeli conflict requires a measured and an arduous mediation process empowered by dialogue that deconstructs conflictive norms and values that lead to peace. The study follows a comparative methodology of the three accords to validate its hypothesis. Hence a matrix that compares the main component of the case studies was conducted. The result showed that the social psychological paradigm with the support of the complex constructivist analysis is able to reach a sustainable peace.